Reporte De Caso Clínico De Equino Con Sepsis Neonatal (2025)
This work was carried out in the period 2024-I in the months of February to May 2024 with the company of Dr. Laura Idrobo in the DIPON facility (General Directorate of the National Police) - Carabineros; where 250 hours of internship were performed as degree work, in which different clinical pathologies are evidenced with greater affectation at the level of the bone system such as: claudications, subsolar abscesses, fractures at the hoof level.